MANAJEMEN SUMBER BELAJAR BERBASIS PLATFORM DIGITAL UNTUK GENERASI Z - Nadira Qayyumi Ilmi; Amrina Rosada; Sulkifli (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
The development of digital technology has transformed the way Generation Z acquires, manages, and utilizes learning resources. As a generation that grew up in a technological environment, Generation Z tends to rely on various digital platforms to support a more flexible, interactive, and accessible learning process. This study aims to examine the management of digital platform-based learning resources to improve learning effectiveness for Generation Z. Learning resource management includes the process of planning, organizing, utilizing, and evaluating various digital learning resources such as Learning Management Systems (LMS), educational social media, learning applications, and digital libraries. This study used a literature study approach with the systematic literature review (SLR) method. The results of the study indicate that the use of digital platforms can increase information accessibility, encourage independent learning, strengthen collaboration, and improve students' digital literacy skills. However, its implementation also faces challenges such as gaps in technology access, low information evaluation skills, and potential distractions from digital media use. Therefore, a planned management strategy, adequate infrastructure support, and strengthening digital literacy are needed so that digital platform-based learning resources can be optimally utilized. With effective management, digital platforms have the potential to become relevant and adaptive learning tools to meet the characteristics and needs of Generation Z in the era of digital transformation,